2019
DOI: 10.1108/afr-10-2018-0082
|View full text |Cite
|
Sign up to set email alerts
|

Premium subsidies and crop insurance demand in Brazil

Abstract: Purpose The purpose of this paper is to examine the effects of premium subsidies provided by the Brazilian government through the Rural Insurance Premium Subvention Program (PSR) on the quantity demanded for crop insurance by grains producers of southern Brazil. Design/methodology/approach A fixed effects model was applied to an unbalanced panel data of municipalities of southern Brazil considering the years between 2006 and 2015. Three measures of crop insurance demand were considered: level of total premiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 15 publications
3
5
0
Order By: Relevance
“…Studies about the effect of the intervention program in addition to crop insurance premium subsidy have not been conducted. Therefore, considering the premium subsidy and other programs are part of the public intervention, this research confirmed the previous study conducted by Goodwin et al (2004) and Lavorato et al (2019) that showed premium subsidy has a positive effect on the crop insurance demand. In line with the positive impact, it is unavoidable that farmers will demand a higher subsidy than the current scheme, as confirmed by Ambarawati (2018).…”
Section: The Effect Of Government Program To Stimulate Farmer Participation In Autpsupporting
confidence: 88%
See 1 more Smart Citation
“…Studies about the effect of the intervention program in addition to crop insurance premium subsidy have not been conducted. Therefore, considering the premium subsidy and other programs are part of the public intervention, this research confirmed the previous study conducted by Goodwin et al (2004) and Lavorato et al (2019) that showed premium subsidy has a positive effect on the crop insurance demand. In line with the positive impact, it is unavoidable that farmers will demand a higher subsidy than the current scheme, as confirmed by Ambarawati (2018).…”
Section: The Effect Of Government Program To Stimulate Farmer Participation In Autpsupporting
confidence: 88%
“…This target only saves around 6% of Indonesia's total agricultural land, which amounts to 15 million hectares. Literature suggests the existence of a positive, although inelastic, effect of the subsidy level on demand for crop insurance (Goodwin et al 2004, Lavorato et al 2019. Meanwhile, higher premium subsidies induce more insurance coverage, lowering farmers' risk (Yu et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This approach is extended by Collins (1985), who explored the effects of increased farm income on balancing risk hypothesis, and also Featherstone et al (1988), who considered the likelihood of equity loss based on the leverage of the financial contracts. Lavorato et al (2020) found reciprocal positive feedback between insurance and credit policies, which corroborated the balancing risk hypothesis. More specifically, farmers would leverage loans as they reduce their business risk, with practices such as production diversification, hedging strategies and acquiring rural insurance.…”
Section: Rural Credit and Rural Insurance Policiessupporting
confidence: 71%
“…As a consequence, government subvention can increase insurance supply, leading to stable farmer's revenues, which might increase agricultural production (Aimin, 2010;Backus et al, 1997). Lavorato et al (2020) found a positive effect of the premium subsidy on insurance demand in Brazil. Besides rural credit and rural insurance, Brazil's government also offers policies on agricultural commercialization, especially on price support.…”
Section: Rural Credit and Rural Insurance Policiesmentioning
confidence: 97%
See 1 more Smart Citation